2008
DOI: 10.1038/sj.bjc.6604281
|View full text |Cite|
|
Sign up to set email alerts
|

The E3 ubiquitin ligase EDD is an adverse prognostic factor for serous epithelial ovarian cancer and modulates cisplatin resistance in vitro

Abstract: Despite a high initial response rate to first-line platinum/paclitaxel chemotherapy, most women with epithelial ovarian cancer relapse with recurrent disease that becomes refractory to further cytotoxic treatment. We have previously shown that the E3 ubiquitin ligase, EDD, a regulator of DNA damage responses, is amplified and overexpressed in serous ovarian carcinoma. Given that DNA damage pathways are linked to platinum resistance, the aim of this study was to determine if EDD expression was associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 41 publications
4
51
0
1
Order By: Relevance
“…Evidence suggesting an involvement of EDD1 in human cancer includes the finding from several studies demonstrating that the degree by which EDD1 interacts with CIB, TOPBP1, and CHK2 is regulated by the DNA damage response (22,24,25). Moreover, EDD1 expression has been shown to functionally correlate with the responsiveness of patients with ovarian cancer to DNA-damaging cytotoxic therapies (26). Several reports have also demonstrated that EDD1 is overexpressed in a high percentage of cancers, consistent with a pattern that correlates with an increased copy number of the EDD1 locus (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggesting an involvement of EDD1 in human cancer includes the finding from several studies demonstrating that the degree by which EDD1 interacts with CIB, TOPBP1, and CHK2 is regulated by the DNA damage response (22,24,25). Moreover, EDD1 expression has been shown to functionally correlate with the responsiveness of patients with ovarian cancer to DNA-damaging cytotoxic therapies (26). Several reports have also demonstrated that EDD1 is overexpressed in a high percentage of cancers, consistent with a pattern that correlates with an increased copy number of the EDD1 locus (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…EDD is frequently amplified and overexpressed in many types of cancer, including ovarian cancer, breast cancer, hepatocellular carcinoma, squamous cell carcinoma of the tongue, and metastatic melanoma (20). Furthermore, high nuclear EDD expression in serous ovarian carcinoma is associated with adverse prognosis, and depletion of EDD inhibits the growth of cisplatin-resistant ovarian cancer cells and partially restores their platinum sensitivity (43). It would be interesting to investigate whether the association of EDD overexpression with poor clinical outcome in cancer patients is related to its activity in suppressing p53 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the gene for UBR5 (EDD), one of N-recognins (Fig. 1A), is often amplified in ovarian carcinoma, and it is an adverse prognostic factor in this disease (40).…”
Section: Discussionmentioning
confidence: 99%